Measuring Chaoui Linguistic Variation in the City of Oum El Bouaghi: A Dialectometric Study - Bouri, Hadj (Milev Journal of Research and Studies, 2017)
This study aims at measuring the impact of geographic distance on the linguistic difference. A questionnaire was designed to elicit Chaoui lexis based on the Swadesh list. A levenshtein algorithm was applied to measure the linguistic distance between all the municipalities of the city of Oum El Bouaghi. Also, a correlation experimental design was administered to conduct the study and measure how language varies according to the geographical landscape of the Berber region of the Chaouia. The results show a positive influence of the geographical distance on the Chaoui linguistic diversity and the alternative hypothesis was confirmed. The implementation of inferential statistics along with the levenshtein algorithm helps in understanding how the Berber language intersect with its geographical landscape.